FLEXURAL BEHAVIOR OF A CONCRETE BEAM REINFORCED WITH METAL REBARS PRODUCED FROM A PSEUDO-ELASTIC NICKEL-TITANIUM ALLOY - Silva, Jeanisson Cesar Mariano; Ferreira, Jorge; Sousa, Douglas (Journal of Applied Engineering Science, 2023)
The use of concrete in the construction industry is widespread throughout the world, which increases the need for a better characterization of its technical aspects. In particular, there is a need for a better understanding of its poor performance when subjected to dynamic loads, which occurs due to its great stiffness and its little (if any) deformation capacity. Knowing that one of the ways to mitigate the poor behavior of concrete in case of dynamic loads is by improving the deformation capacity or ductility of the metallic reinforcement, the proposal to explore the behavior of a concrete beam reinforced with metallic rebars produced from a pseudo-elastic Nickel-Titanium alloy becomes highly desirable. This experimental research aims to verify the flexural behavior of a concrete beam reinforced with Nickel-Titanium rebars. In this regard, the requirements suggested by the technical standard in force were carefully followed, relying mainly on the international standard ASTM C78. Concrete specimens were produced either reinforced with conventional steel rebars; or reinforced with Nickel-Titanium rebars. The results showed that, although the Nickel-Titanium rebars specimens presented a modulus of rupture 26.48% lower, their displacement was about 642.79% greater in relation to specimens with conventional steel rebars, in addition to presenting a partial recovery of the beam's initial position even after complete concrete breakage.
Keywords: smart materials, flexural test, special structures